INTEGRATED MENTAL DEVELOPMENT OF CHILDREN WITH SPECIAL EDUCATIONAL NEEDS OF OLDER PRE-SCHOOL AGE BY MEANS OF MUSICAL INFLUENCE (Psychology Travelogs, 2023)
In the spheres of modern society, a serious revaluation of values is taking place, the content of the entire social existence and consciousness is changing, along with it, education is also changing no less. The disclosure and understanding of the deep layers of the inner world of a person in its integrity, the inseparable totality of his spiritual and emotional, personal and intellectual development prompts scientists to direct their efforts to the integration of knowledge, to the connection of knowledge with humanistic values, where people who carry them are given the opportunity to self-realize.It has been clarified that the comprehensiveness of musical education acts as one of the effective ways of moral enrichment of the formation of the child's personality, the activation of his mental activity, and the improvement of vitality. The article examines the integrated mental development of children with special educational needs of older preschool age by means of musical influence. Listening to music is a tool that can be used at the earliest stages of a child's development. Listening, and later imitating, brings up quality criteria in children at a subconscious level, with the help of which in the future the child will be able to orient himself in the value of certain examples of musical art.A child, communicating with music, develops comprehensively, the child's physical appearance improves, and harmonious relationships are established. Musically rhythmic movements encourage correct posture, coordination of movements, their flexibility and plasticity. This is especially relevant for children with mental retardation.
Keywords: musical influence; children with special educational needs; development; preschool age; mental retardation